The Impact of Polypharmacy on Patient Outcomes in Older Adults With Cancer. Issue 4 (July 2017) - Nightingale, Ginah; Skonecki, Emily; Boparai, Manpreet K.
Abstract : Abstract: Polypharmacy is prevalent in older adults with cancer and may be advantageous for the management of certain chronic disease states, but uncertainty exists regarding potential hazards and consequences. Cancer-related therapy adds to the prevalence of polypharmacy, which can lead to compromised cancer management plans (i.e., postoperative complications, treatment delays, and/or premature treatment discontinuation). Polypharmacy has been identified as one of the domains commonly included in the Comprehensive Geriatric Assessment likely because of the potential influence on health outcomes. This review summarizes existing evidence regarding health outcomes associated with polypharmacy in older adults with cancer. Preliminary evidence demonstrated that relationships exist between polypharmacy and health outcomes including adverse drug events, falls, frailty, hospitalization, postoperative complications, and mortality. This research is limited by study confounders, inconsistent definitions for polypharmacy, heterogeneous cancer types and stages, and the complex relationship between medication regimens and outcomes. Additional studies are needed to enhance the accuracy and replicability of this research.